The Effect of Different Doses of Salt Stress on Germination and Emergence in Cannabis (Cannabis sativa L.) Seed Treated with Pre-Salicylic Acid - Gul, Volkan; Sefaoglu, Fırat; Cetinkaya, Hatice; Dinler, Burcu Seckin (FapUNIFESP (SciELO), 2024)
Abstract It is known that salinity stress, one of the abiotic stress factors, significantly limits the germination, growth, development, and crop yield of plants. Therefore, this study was conducted to evaluate the effects of salinity (control, 50, 100 ve 150 mM) on seed germination and the effect of salicylic acid (control, 0.25, 0.50, 0.75 ve 1.00 mM) on seed germination to improve salt tolerance in cannabis seeds. The physiological characteristics of the plant, such as germination percentage, germination duration, germination index, radicle length, plumule length, wet radicle weight, dry radicle weight, wet plumule weight, and dry plumule weight, were analyzed. Depending on the salinity application dose, it was observed that there was a significant decrease in the germination parameters of cannabis seeds compared to the control. It was observed that salicylic acid treatments under salinity stress positively affected all the characters examined and reduced germination arrest due to increasing concentration levels. Although it is recommended to prepare seeds with 0.5 mM salicylic acid pre-application dose against salt stress of the cannabis plant,it is essential to expand the studies on its transfer to practice. As a result, salicylic acid will provide positive results that can be transferred to practice by increasing the resistance of cannabis plants against salinity, especially in agricultural soils with salt problems, as it will be more sensitive to pests and diseases.
Keywords: germination percentage; salicylic acid; Cannabis sativa L.; Cannabis sativa L; hemp seed; TP248.13-248.65; salt stress; Biotechnology